2010
DOI: 10.1177/0042098009356127
|View full text |Cite
|
Sign up to set email alerts
|

Commuting Times: Is There Any Penalty for Immigrants?

Abstract: Esta es la versión de autor del artículo publicado en:This is an author produced version of a paper published in: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 49 publications
3
22
0
2
Order By: Relevance
“…En cuanto a las características de la movilidad, el tiempo empleado en los viajes al lugar de trabajo ha sido utilizado por algunos autores (Blázquez, Llano & Moral, 2010) como un buen indicador para comprobar la teoría del spatial mismatch (Painter, Liu & Duan, 2007), según la cual la creciente diferenciación entre una residencia localizada en su mayoría en los centros de las grandes urbes, y unos lugares de trabajo que se desplazan continuamente hacia el extrarradio, provoca una situación de desventaja laboral para los extranjeros, resultando en un menor acceso a la ocupación, el consiguiente aumento del paro y, finalmente, un mayor tiempo empleado entre desplazamiento y trabajo entre los ocupados. La única contrapartida a esta situación es la mayor capacidad de adaptación de la población inmigrante, debido a una mayor movilidad residencial.…”
Section: Sobre La Movilidad Diaria De Los Inmigrantesunclassified
“…En cuanto a las características de la movilidad, el tiempo empleado en los viajes al lugar de trabajo ha sido utilizado por algunos autores (Blázquez, Llano & Moral, 2010) como un buen indicador para comprobar la teoría del spatial mismatch (Painter, Liu & Duan, 2007), según la cual la creciente diferenciación entre una residencia localizada en su mayoría en los centros de las grandes urbes, y unos lugares de trabajo que se desplazan continuamente hacia el extrarradio, provoca una situación de desventaja laboral para los extranjeros, resultando en un menor acceso a la ocupación, el consiguiente aumento del paro y, finalmente, un mayor tiempo empleado entre desplazamiento y trabajo entre los ocupados. La única contrapartida a esta situación es la mayor capacidad de adaptación de la población inmigrante, debido a una mayor movilidad residencial.…”
Section: Sobre La Movilidad Diaria De Los Inmigrantesunclassified
“…Blazquez et al (2010) and Preston et al (1998) have each examined commuting time as a barrier to work and as a possible indicator of residential segregation and spatial mismatches in skill availability and needs. Qualitative and smallsample studies by Anastario and Schmalzbauer (2008), Bloch (1976), and Münscher 4 (1984) indicate that household responsibilities may hinder women's economic assimilation.…”
Section: Why Study Immigrants' Time Use?mentioning
confidence: 99%
“…They found that reported commutes were longer for immigrants than for natives but that differences associated with gender, race and ethnicity exceeded those associated with nativity status. Blazquez et al (2010) Volunteering. Osili and Xie (2009) They also found evidence of acculturation in health behaviors and obesity.…”
Section: Work Hoursmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a number of papers dealing with the measurement of residential segregation in Spain. For example, Pareja-Eastaway (2009) and García-López (2012) measure segregation in Barcelona, while Blázquez, Llano, and Moral (2010) relate commuting times to segregation (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004), and Echazarra (2010) studies the correlates of neighborhood segregation (2001)(2002)(2003)(2004)(2005)(2006) in Madrid. Bosch, Carnero, and Farré (2010) study the existence of ethnic discrimination against immigrants in the rental market.…”
Section: Introductionmentioning
confidence: 99%